Peran Guru IPS dalam Meningkatkan Kesadaran Siswa pada Isu-Isu Lingkungan Madrasah di MTsN 5 Tulungagung - Ulfatun Nadhifah; Jani Jani (Universitas 45 Surabaya, 2024)
This research is motivated by the need to examine the role of Social Studies teachers in increasing student awareness of environmental issues at MTsN 5 Tulungagung. Environmental issues are an important topic in modern education due to their relevance to ecosystem sustainability and human quality of life. Social studies teachers have strategies to instill environmental care values through collaboration between school parties and the role of teachers as innovators. This thesis focuses on: 1) How social studies teachers play a role in increasing student awareness of environmental issues at MTsN 5 Tulungagung, 2) What strategies are used by social studies teachers to increase student awareness of environmental issues at MTsN 5 Tulungagung, 3) What are the supporting and inhibiting factors for social studies teachers in increasing student awareness of environmental issues at MTsN 5 Tulungagung. The objectives of this study are: 1) To determine the role of social studies teachers in increasing student awareness of environmental issues at MTsN 5 Tulungagung, 2) To determine what strategies are used by social studies teachers to increase student awareness of environmental issues at MTsN 5 Tulungagung, 3) To determine the supporting and inhibiting factors for social studies teachers in increasing student awareness of environmental issues. This research uses a descriptive qualitative research method. Data were obtained through interviews, observation, and documentation. Observations were conducted to get a closer look at the object under study, interviews were used to identify or find problems openly at MTsN 5 Tulungagung, while documentation was used to collect data by investigating existing documents and is a place to prepare a number of data so that researchers get maximum information that can describe the condition of the object under study correctly. The results of this study indicate that the role of social studies teachers in increasing student awareness of environmental issues at MTsN 5 Tulungagung is by using the following methods: first, strengthening values and character such as; the value of responsibility, the value of caring and empathy, the value of discipline, and the value of mutual cooperation. Then the second method is an interactive teaching strategy. The strategy used by social studies teachers to increase student awareness of environmental issues at MTsN 5 Tulungagung is: the strategy of social studies teachers as innovators and collaborating between school parties. Supporting and inhibiting factors for social studies teachers in increasing student awareness of environmental issues at MTsN 5 Tulungagung include supporting factors such as school policies and collaboration between teachers, while the inhibiting factors themselves are both from the students themselves and internal factors such as from the canteen.